The Influence of Organizational Culture to Supply Chain Performance by Moderating Effect of Transformational Leadership on Manufacturing Company in Riau Island Province - nasar buntu laulita (Journal of Business Studies and Management Review, 2020)
The purpose of this study is to know the relationship of organizational cultures to supply chain performance by moderating effect of supply chain transformational leadership style. The explanatory research was used by testing eight hypotheses for total samples from 171 manufacturing companies being represented by manager in supply chain management divisions of total 850 companies in Riau Island Province as one of region in Indonesia. SEM (Structural Equation Model) was used to analyze the data after getting primary data through questionare. The result of analyze found that: (1a) Development Culture is not significant to affect Supply Chain Performance; (1b) Transformational Leadership Style is significant to moderate relationship between Development Culture and Supply Chain Performance; (2a) Group Culture is significant to affect Supply Chain Performance and positively; (2b) Transformational Leadership Style is significant to moderate relationship between Group Culture and Supply Chain Performance; (3a) Rationale Culture is significant to affect Supply Chain Performance and positively; (3b) Transformational Leadership Style is significant to moderate relationship between Rationale Culture and Supply Chain Performance; (4a) Hierarchy Culture is significant to affect Supply Chain Performance; (4b) Transformational Leadership Style is significant to moderate relationship between Hierarchy Culture and Supply Chain Performance. The managerial implication of this research is as a guidance for decision maker in the company or manager in the supply chain management to implement suitable organizational culture and consider the effect of supply chain transformational leadership style to improve Supply Chain Performance.